2001
DOI: 10.1074/jbc.m008663200
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of the β4 Integrin Cytoplasmic Domain Mediates Shc Signaling to Extracellular Signal-regulated Kinase and Antagonizes Formation of Hemidesmosomes

Abstract: Ligation of the ␣ 6 ␤ 4 integrin induces tyrosine phosphorylation of the ␤ 4 cytoplasmic domain, followed by recruitment of the adaptor protein Shc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
119
1
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 42 publications
9
119
1
3
Order By: Relevance
“…This conclusion stands in clear contrast to prior studies indicating that TAM-mutant ␤ 4 localizes efficiently to endogenous HDlike adhesions of 804G cells and that it promotes assembly of HD-like adhesions in (immortalized) PA-JEB keratinocytes (22,23), thus indicated that ␤ 4 TAM is dispensable for HD formation (22).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…This conclusion stands in clear contrast to prior studies indicating that TAM-mutant ␤ 4 localizes efficiently to endogenous HDlike adhesions of 804G cells and that it promotes assembly of HD-like adhesions in (immortalized) PA-JEB keratinocytes (22,23), thus indicated that ␤ 4 TAM is dispensable for HD formation (22).…”
Section: Discussioncontrasting
confidence: 54%
“…The origin and nature of this variant form remain to be established. We have observed that this variant form of ␤ 4 and a canonical form carrying phenylalanine substitutions at Tyr-1422 or Tyr-1440 are both normally incorporated in the HD-like adhesions of 804G cells (23). However, a mutant ␤ 4 carrying both modifications is not, as shown previously (18).…”
mentioning
confidence: 47%
See 1 more Smart Citation
“…The adaptor protein Shc, recently shown to participate in FAK-independent signaling from antibody-ligated ␤ 4 integrin to ERK (37) and from Met receptor tyrosine kinase-activated ␤ 4 integrin to Ras-and PI3K-dependent pathways (20,38), seemed not to be involved in the ␤ 4 -mCLCA1-mediated signaling in our tumor model. Anti-␤ 4 , anti-HA, and anti-Grb2 immunoprecipitates prepared from FAK-HA-transfected B16-F10 cells bound to mCLCA1 failed to co-precipitate and activate Shc B16-F10 co-transfected with GFP/wtFAK and GFP/FRNK were seeded onto monolayers of BAEC that constitutively express bCLCA2 shown to mediate strong B16-F10 adhesion (5,6).…”
Section: Discussionmentioning
confidence: 85%
“…Assembly of hemidesmosomes depends on both ␤4 TAM motif and its membrane proximal portion (Gap). 56 LMP2A-mediated modulation of B-cell receptor signaling was affected by mutations in either of the 2 tyrosine residues alone of the LMP2A ITAM motif, while only mutations in both sites restored the hTERT promoter activity. This suggests another distinct difference of LMP2A regulation in epithelial cells in contrast to B-cells.…”
Section: Discussionmentioning
confidence: 99%